ANSWER
See graph
EXPLANATION
We need to find the y-values for the ordered pairs by substituting the x-value in to the relation
when
[tex]x = - 2[/tex]
[tex]y = 3( - 2) + 3[/tex]
[tex]y = - 6 + 3[/tex]
[tex]y = - 3[/tex]
This gives the ordered pair
[tex](-2,-3)[/tex]
when
[tex]x = 1[/tex]
.
[tex]y = 3(1) + 3[/tex]
[tex]y = 3 + 3[/tex]
[tex]y = 6[/tex]
This also gives the ordered pair
[tex](1,6)[/tex]
when
[tex]x = 2[/tex]
[tex]y = 3(2) + 3[/tex]
.
[tex]y = 9[/tex]
This also gives the ordered pair,
[tex](2,9)[/tex]
We now plot all the ordered pairs and draw a line through them.